2001
DOI: 10.1002/erv.372
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐cultural study on eating attitudes and behaviours in two Spanish‐speaking countries: Spain and Mexico

Abstract: Cross-cultural studies can provide important data on the in¯uence of cultural factors in the growth and control of eating disorders and their symptoms. If, moreover, those studies deal with the same language but different contexts, the comparison may be richer and the knowledge derived more signi®cant. The main aim of the present study is to identify the prevalence of eating disorder and body dissatisfaction symptoms, as well as the factors which may in¯uence them, in two samples of ®rst-year female university… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
8

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 14 publications
0
10
0
8
Order By: Relevance
“…Results are fairly inconsistent when it comes to these comparisons, with two studies suggesting (in line with the pattern of affluence) that Spanish females are more dissatisfied with their bodies than Mexican females (Raich et al, 2001;Toro et al, 2006) but two studies suggesting rather the opposite (Goméz-Peresmitré & Garcia, 2000;Goméz-Peresmitré & García, 2002). Perhaps this particular comparison is an additionally complex one since both countries are highly influenced by the Western lifestyle.…”
Section: Cultural Differences In Body Dissatisfactionmentioning
confidence: 89%
“…Results are fairly inconsistent when it comes to these comparisons, with two studies suggesting (in line with the pattern of affluence) that Spanish females are more dissatisfied with their bodies than Mexican females (Raich et al, 2001;Toro et al, 2006) but two studies suggesting rather the opposite (Goméz-Peresmitré & Garcia, 2000;Goméz-Peresmitré & García, 2002). Perhaps this particular comparison is an additionally complex one since both countries are highly influenced by the Western lifestyle.…”
Section: Cultural Differences In Body Dissatisfactionmentioning
confidence: 89%
“…Existing research comparing Spanish, Mexican, Mexican American, and European American women on eating disorder symptoms, body dissatisfaction, and physical ideals has yielded mixed results. In a comparison of eating disorder symptoms in Spain and Mexico, Raich et al (2001) found eating disorder symptoms and body dissatisfaction to be more prevalent and severe in Spanish women than in Mexican women. Peresmitre and Garcia (2000) found that Mexican women selected a thinner ideal figure and assigned more importance to physical appearance in social situations with men and at work than Spanish women.…”
Section: Spain and Eating Disorder Symptomatologymentioning
confidence: 95%
“…In comparison to Caucasian women, African American women preferred larger ideal body shapes, reported less body dissatisfaction (Ashley, Smith, Robinson, & Richardson, 1996;Miller, Gleaves, Hirsch, Green, Snow, & Corbett, 2000), and had lower rates of eating disorders (Abrams, Allen, & Gray, 1993;Rucker & Cash, 1992). BMI levels have also been found to be related to increased risk of eating disorders among Mexican and Spanish women (Raich et al 2001) and a multiethnic sample of British adolescents (Thomas, James, & Bachmann, 2002).…”
Section: Introductionmentioning
confidence: 93%